The Role of Individual and Group Counseling for Moral Coaching - Abdur Ro’uf; Muhammad Arfan Mu’ammar; Mastoh Chesoh (The Indonesian Institute of Science and Technology Research, 2022)
his study discusses the role of individual and group counselling, which aims to foster student morals. The subject of this study was Madrasah Tsanawiyah (Islamic Junior School) in Madura. Metode research used descriptive qualitative—data collection through observation, interviews and documentation. Data is analyzed through the process of data reduction, data presentation, and inference. Information is considered valid regarding credibility, transferability, dependability and affirmability. The results showed that the morals of the students were already quite good. Individual and group counselling is effective. Some problems are resolved through individual counselling, such as skipping school, being absent, and disturbing friends in class. What is accomplished through group counselling is being late, harassing friends in class, and fighting. The methods of individual and group counselling are almost the same. Supervisors maintain confidentiality and provide a sense of comfort and healing. Teachers provide advice, evaluation and follow-up.